Vključevanje učencev kot deležnikov v načrtovanje samoevalvacije - Zavašnik, Mihaela (Šolsko polje, 2010)
Self-evaluation as a means of quality assessment and assurance in schools has caught much attention during the last decade as schools are increasingy becoming more accountable for quality demanded by various stakeholders, which have a right and are entitled to access and use of school achievements. In order to carry out self-evaluation properly and successfully, it is necessary for schools to open their doors and invite various stakeholders to cooperate in school improvement processes. The article focuses on a small scale qualitative research about involving students as stakeholders in planning self-evaluation. The analysis shows that it is much easier not to involve stakeholders than to involve them. Once the decision is made to involve stakeholders actively, the school and the stakeholders must be prepared to face the problems, which are likely to cause worry and difficulty with the self-evaluation process. The biggest problems seem to be the complexities of logistical arrangements and available resources (especially time), the decision about informing and/or negotiating (divergent) viewpoints and the (un)awareness of the need and aim of students' involvement. However, it can also be summarized that the students' involvement represents a strong and meaningful way of entering a dialogue, and opens numerous important questions regarding the enhanced cooperation and critical reflections about stakeholder involvement in school processes. The (head)teachers noted that the students described their involvement as positive, fun and interesting. Moreover, the students' readiness to become actively involved in quality assessment and assurance processes can as well be understood as a demonstration of their responsibility and commitment to school improvement.
Keywords: deležniki; kakovost v izobraževanju; načrtovanje; planning; quality in education; samoevalvacija; self-evaluation; stakeholders; vzgoja in izobraževanje